A COMPARATIVE STUDY OF ISLAMIC CALLIGRAPHIC PAINTING IN MALAYSIA AND IRAN: KAJIAN PERBANDINGAN ANTARA SENI LUKIS KHAT DI MALAYSIA DAN IRAN - Seyedi, Bibi Maliheh; Hamidon, Nor Azlin; N. Ross, Lawrence (Jurnal Pengajian Melayu (JOMAS), 2017)
This article compares Islamic calligraphy paintings produced in Iran and Malaysia, since the 1950’s as a means to better understand their arts educational systems, their distinctive artistic identities, and provide closer looks at the works of significant artists from each country. It examines twelve works using a framework that examines elements of form, context, content, and Islamic unity (tawhid), as a means to better understand contemporary developments as calligraphy and painting techniques converge. Keywords: Islamic calligraphy, painting, Malaysia, Iran. Artikel ini mengenai kajian perbandingan seni kaligrafi Islam antara Iran dan Malaysia sejak dekad 1950-an untuk memahami sistem pendidikan seni kedua-dua buah negara, identiti kesenian yang berbeza dan menyediakan pandangan lebih dekat tentang karya-karya artis dari setiap negara. Ia juga mengkaji dua belas karya menggunakan kerangka kerja yang memeriksa elemen rupa, konteks dan isi, dan juga kesatuan Islam (tawhid) sebagai kaedah yang lebih baik dalam memahami pembangunan seni kontemporari dan pertemuan teknik lukisan. Kata Kunci: kaligrafi Islam, lukisan, Malaysia, Iran.